Análisis comparativo de la operación y rentabilidad de la tecnología wimax en Guayaquil - Mayorga Naranjo, Michael Alejandro (2009)
The present work will realise an analysis of economic and technical yield between two companies of telecommunications; El Grupo TV Cable and TELMEX, that use WiMAX as last mile technology to provide services of voice and data; El Grupo TV Cable already uses for three years this technology and TELMEX is planning it to for the next years. The technical comparison was made it through interviews done to these companies having allowed know and understand the functionality us of the network WiMAX, in each of them. The economic comparison was made with interviews and investigation done to suppliers of equipment WiMAX such as Airspan and Alvarion for TV Cable and Telmex. The operation analysis could be realised thanks to the data collected in the course of this study visiting these companies to determine the advantages and disadvantages that own each their networks. The yield analysis could be obtained using methods of evaluation of projects with real data collected by their respective suppliers of WiMAX equipment, but detailed present costs in this study that are involved with this type of networks. At the end of this work it is hoped to conclude which of these two companies has one better economic and technical yield at the time of to have used WiMAX like technology of last mile.